Financial Literacy and Consumer Awareness Survey in the West Bank and Gaza - Riyada Consulting and Training (World Bank, Washington, DC, 2017)
This study of financial literacy and consumer financial awareness of the Palestinian people was conducted via a literature review and a comprehensive household survey in the West Bank and Gaza in 2011. It was commissioned by the World Bank (WB) under the global program on consumer protection and financial literacy (CPFL) that was launched in 2010 to help targeted countries achieve better consumer protection in financial services. The survey focuses on key segments of the financial services sector such as banking, insurance, and microfinance, and it was designed with the goal of contributing to the development of the financial markets and national development agenda of the West Bank and Gaza. The main objective of the survey is to evaluate the levels of financial awareness and familiarity with financial services providers, attitudes, and opinions regarding the financial markets, household management of financial resources, and use of financial services. The survey subsequently aims to identify appropriate methods for expanding consumer education and strengthening consumer rights in the West Bank and Gaza. The collected data can be used to develop a toolkit for financial services and consumer protection in the West Bank and Gaza.